Analysis Of Lead (Pb), Zing (Zn), and Copper (Cu) Levels in Catfish (Pangasius hypophthalmus) From Kampar Regency Using Atomic Absorption Spectrophotometry - Subardi Bali; Vonny Kurnia Utama; Sri Kartini; Dwi Hestia Anjani (Jurnal Ilmu Kesehatan Abdurrab, 2026)
Heavy metal contamination in aquatic environments has become a serious issue due to its potential adverse effects on human health through the food chain. This study aims to determine the concentrations of lead (Pb), zinc (Zn), and copper (Cu) in catfish (Pangasius hypopthalmus) collected from three different locations: floating cages under the Rantau Berangin Bridge, the Danau Bingkuang Bridge, and a cultivation pond in Silam Village. The samples were analyzed using Atomic Absorption Spectrophotometry (AAS) after digestion with a microwave digester. The results showed Pb concentrations in samples JRB 1, JRB 2, JDB 1, JDB 2, KDS 1, and KDS 2 were 479 mg/kg; 16.27 mg/kg; 165.68 mg/kg; 356.21 mg/kg; 99.6 mg/kg; and 336.57 mg/kg, respectively. Zn concentrations were 8.05 mg/kg; 0 mg/kg; 2.45 mg/kg; 1.09 mg/kg; 24.3 mg/kg; and 0.490 mg/kg, while Cu concentrations were 2.84 mg/kg; 2.81 mg/kg; 1.76 mg/kg; 0 mg/kg; 15.65 mg/kg; and 0 mg/kg, respectively. All Pb levels exceeded the maximum limit set by SNI 2729:2021, which is 0.3 mg/kg. Meanwhile, Zn and Cu levels remained within safe limits based on the decree of the Director General of BPOM No. 03725/B/SK/VII/89. Based on these findings, it can be concluded that heavy metal contamination, particularly by Pb, was present in the tested samples, rendering them unsuitable for consumption without further monitoring and testing